Proceedings of the ACM SIGCHI Conference on Human Factors in Computing Systems 1997
DOI: 10.1145/258549.258724
|View full text |Cite
|
Sign up to set email alerts
|

Making computers easier for older adults to use

Abstract: The normal effects of aging include some decline in cognitive, perceptual, and motor abilities. This can have a negative effect on the performance of a number of tasks, including basic pointing and selection tasks common to today's graphical user interfaces. This paper describes a study of the effectiveness of two interaction techniques: area cursors and sticky icons, in improving the performance of older adults in basic selection tasks. The study described here indicates that when combined, these techniques c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
235
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(244 citation statements)
references
References 8 publications
2
235
0
7
Order By: Relevance
“…In 2010, older workers accounted for 17% -31% of the population of the European Union, while it is forecast that by 2050 these rates will have more than doubled [8]. Intimately related to issues involved in the design of new websites or applications for seniors is the importance of understanding the highly complex process of human ageing as cognitive, perceptual and motor abilities decline with age and thus render more difficult many tasks, including basic pointing and selecting, that are commonly used in interaction with a device [9], [10], [11], [12].…”
Section: B Ageingmentioning
confidence: 99%
“…In 2010, older workers accounted for 17% -31% of the population of the European Union, while it is forecast that by 2050 these rates will have more than doubled [8]. Intimately related to issues involved in the design of new websites or applications for seniors is the importance of understanding the highly complex process of human ageing as cognitive, perceptual and motor abilities decline with age and thus render more difficult many tasks, including basic pointing and selecting, that are commonly used in interaction with a device [9], [10], [11], [12].…”
Section: B Ageingmentioning
confidence: 99%
“…For haptic assistance to be effective in realworld GUIs it needs to be generalisable for different target sizes and shape. Previous studies have often reported that the greatest improvements in performance have been observed when the assistance is used with smaller targets (Worden et al, 1997;Cockburn and Brewster, 2005). A further experiment has been conducted to investigate the effect of target size and shape on the performance of the two deformable techniques.…”
Section: Experiments 2 -The Effect Of Target Size and Shapementioning
confidence: 99%
“…While the Thornton and Dumke (2005) metaanalysis suggested a negative relationship between age and solution quality (see also Finucane et al, 2002, other studies have found age invariance in solution quality. Patrick (1995) failed to find age differences in solution quality in a highly structured car-shopping task, as did Walker et al (1997) in a driving decisions task and Meyer et al (1995) in a breast cancer decision-making task. In the driving study, older adults tended to vary their decisions more (i.e., greater inconsistency) and have less confidence about their decisions, but the overall quality of younger and older adults' route decisions was similar (Walker et al, 1997).…”
Section: Decision Makingmentioning
confidence: 99%
“…Patrick (1995) failed to find age differences in solution quality in a highly structured car-shopping task, as did Walker et al (1997) in a driving decisions task and Meyer et al (1995) in a breast cancer decision-making task. In the driving study, older adults tended to vary their decisions more (i.e., greater inconsistency) and have less confidence about their decisions, but the overall quality of younger and older adults' route decisions was similar (Walker et al, 1997). Kim and Hasher (2005) actually found a performance advantage for older adults relative to undergraduates.…”
Section: Decision Makingmentioning
confidence: 99%